2015
DOI: 10.35386/ser.v16i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Patterns of Study and Self-Concept on Students’ Academic Performance in Borno State College of Education: Implications for Counselling

Abstract: This is a correlational study designed to determine the relationship between patterns of study and self-concept on students’ academic performance in Colleges of Education in Borno State.  The study set two research objectives and tested two research hypotheses. Conceptual framework was applied to patterns of study and humanistic approach was applied to self-concept. The target population for this study was 4,517 students who had registered in NCE awarding institutions in Borno State. Purposive sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…This is because the educational system provided equal opportunities and eliminated gender bias in Biology for both boys and girls. The finding agrees with Goni et al (2015), who revealed no significant differences between male and female students' academic performance. It does not agree with Unity and Igbudu (2015), who stated that there is a gender difference in students' academic achievement.…”
Section: Discussionsupporting
confidence: 91%
“…This is because the educational system provided equal opportunities and eliminated gender bias in Biology for both boys and girls. The finding agrees with Goni et al (2015), who revealed no significant differences between male and female students' academic performance. It does not agree with Unity and Igbudu (2015), who stated that there is a gender difference in students' academic achievement.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study reflected that male and female undergraduates at universities in Khyber Pakhtunkhwa had no significant differences in academic performance in terms of academic scores. Goni et al (2015), Regis-Onuoha and Chukwu (2022) also come up with similar findings, claiming that gender findings do not significantly affect academic performance. Lakhan et al (2021) also reported no significant difference in academic performance between both genders.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research (Goni et al, 2015;Peng & Kievit, 2020) has investigated gender differences in academic achievement. It has been revealed that an individual's background traits substantially impact their cognitive abilities, a crucial factor in determining academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the gender of the children and the self concept scores of females and males were found to be very close to each other. Although there are studies reporting the similarity of the concept of self according to the gender (Aral & Koksal,1999;Ocak & Sarlik,2016;Bayraktar Erten & Erten, 2014;Goni & Bello, 2016;Ozmentes, 2014;Secer, İlbay, Ay & Ciftci, 2012), there are also opposite findings reported so far (Can, 2015;Halici, 2005;Hyun, Kim & Kim, 2004;Janik & Jurak, 2014;Kilicarslan,2012;Koksal Akyol & Sali, 2013). Ercan (2005), Cevher and Bulus (2006), found that females had a higher self-perception than males in their pre-school years while Seremet (2006) asserted that self-perceptions of males were more positive compared to those of females in the pre-school period.…”
Section: Discussionmentioning
confidence: 94%